Anti-fibrosis effect and its mechanism of atractylenolide III on post-traumatic extending knee joint contracture in rats - Bin-Bin Zhang; Lei Xu; Quan-Bing Zhang; Yan Wang; Chen Chen; Jin-Niu Zhang; Xian-Liang Rao; Bing-Jing Zhu; Xue-Ming Li; De-Ting Zhu; Xiu-Li Kan; Jing Mao; et al. (Experimental Gerontology)
Objectives: Atractylenolide III (ATL III) is the major bioactive component found in Atractylodes macrocephala, which has shown a range of benefits in pharmacological studies, including neuroprotection, anti-neuroinflammatory properties, antioxidant effects, anti-allergic effects, anti-cancer properties and antifibrotic abilities. Here, we investigated the therapeutic potential and underlying mechanisms of ATL III in the treatment of post-traumatic joint contracture (PTJC) in rat knees. Methods: The rat PTJC model and TGF-β1-induced a primary synovial fibroblast model were used to observe several fibrotic markers (α-SMA、TGF-β1、FGF2、COL1A1and COL3A1) using histological staining, immunofluorescence and western blot. Additionally, the effects of ATL III on synovial fibroblasts in vitro were evaluated through CCK-8 assays and migration assays to ascertain both cell viability and migratory behaviors. Furthermore, molecular docking studies were performed to elucidate the potential binding affinity of ATL III for Silent information regulator of transcription 1 (Sirt1), thereby providing insights into the underlying molecular mechanisms implicated in fibrosis modulation. Results: ATL III treatment was observed to reduce proliferating cells, inflammatory cells and collagen accumulation in a rat model of traumatic rat knee fibrosis. In vitro, ATL III treatment was found to significantly reduce fibrosis and collagen-associated protein expression and inhibit synovial fibroblast proliferation and migration. Molecular docking identified Sirt1 as a potential target of ATL III. Interestingly, Sirt1 and Smad3 can interact and act to deacetylate Smad3, and in vitro and in vivo ATL III treatment significantly reduced Smad3 acetylation levels. Conclusion: ATL III produces a therapeutic effect on knee fibrosis probably because Sirt1 deacetylates Smad3 and thus relieves knee fibrosis in rats.